2020
DOI: 10.1186/s12890-020-01307-3
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with atorvastatin ameliorates cobra venom factor-induced acute lung inflammation in mice

Abstract: Background The complement system plays a critical role as the pathogenic factor in the models of acute lung injury due to various causes. Cobra venom factor (CVF) is a commonly used complement research tool. The CVF can cause acute inflammation in the lung by producing complement activation components. Atorvastatin (ATR) is a 3-hydroxy-3-methylglutaryl coenzyme A inhibitor approved for control of plasma cholesterol levels. This inhibitor can reduce the acute pulmonary inflammatory response. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Indeed, as a membrane pore–forming protein, the sub-lytic effects of C5b-9 play a more important role in inflammatory response ( Zhang et al, 2021 ). Studies have shown that sub-lytic C5b-9 worked as a trigger of various intracellular signaling processes such as MAPK ( Zhu et al, 2017 ), NF-κB ( Guo et al, 2020 ), and the NLRP3 ( Zhang et al, 2021 ) signaling. However, whether sub-lytic C5b-9 is involved in TCE-induced RTEC pyroptosis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as a membrane pore–forming protein, the sub-lytic effects of C5b-9 play a more important role in inflammatory response ( Zhang et al, 2021 ). Studies have shown that sub-lytic C5b-9 worked as a trigger of various intracellular signaling processes such as MAPK ( Zhu et al, 2017 ), NF-κB ( Guo et al, 2020 ), and the NLRP3 ( Zhang et al, 2021 ) signaling. However, whether sub-lytic C5b-9 is involved in TCE-induced RTEC pyroptosis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-eight mice were randomly divided into six groups ( n = 8 per group): the control group (Control), CVF group (CVF), acteoside 100 mg/kg + CVF group (acteoside 100 mg/kg), acteoside 50 mg/kg + CVF group (acteoside 50 mg/kg), acteoside 20 mg/kg + CVF group (acteoside 20 mg/kg), and PDTC 100 mg/kg + CVF group (PDTC, as a positive control). The mice were subjected to a tail vein injection of CVF (35 μg/kg body weight, dissolved in sterile PBS with PH 7.4) to specifically activate the complement alternative pathway [ 13 , 23 ] and establish the ALI model in mice. The control mice were injected with sterile PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that intravenous injection of CVF can trigger a systemic complement activation, resulting in acute inflammation response and changes in lung function and morphology, which are characterized by increased permeability between pulmonary capillary endothelial cells and alveolar epithelial cells, and the accumulation of a large amount of edema fluid in the alveolar space, which is rich in a variety of inflammatory cells dominated by neutrophils to increase ALI [ 13 , 14 , 15 , 16 ]. Previously, we also have successfully constructed ALI mouse model using CVF as reflected by increases in inflammatory mediators in the lung and morphological evidence of lung damage [ 13 ]. Thus, the CVF-mediated ALI model could be used in exploring the pathological changes and effective medications of lung injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simvastatin and rosuvastatin have anti-inflammatory effects against LPS and virus infection such as influenza A [ 6 , 7 ]. Similarly, atorvastatin also attenuated the lung injury and the inflammatory response induced by various stimuli [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%